A comprehensive framework for modeling requirements of CSCW systems. Issue 5 (21st February 2017) - Teruel, Miguel A.; Navarro, Elena; López‐Jaquero, Víctor; Montero, Francisco; González, Pascual
Abstract: As in any other system, an accurate requirements specification is essential to developing a collaborative system, which has special kinds of requirements that are hard to specify by means of current Requirements Engineering techniques. The Collaborative Systems Requirement Modeling Framework (CSRMF) was developed to address this problem; the original Collaborative Systems Requirement Modeling Language was extended and modeled to properly deal with collaboration and awareness requirements. The developed CSRMF framework consists of 3 components: an Requirements Engineering modeling language able to represent collaboration among users as well as awareness needs, a set of design guidelines that drive Computer Supported Cooperative Work system specification by means of 5 different types of diagrams, and a supporting computer‐ aided software engineering tool to specify and validate Computer Supported Cooperative Work system requirements. CSRMF provides Requirements Engineers with a complete solution to the specification of awareness‐demanding collaborative systems, as they can now take advantage of a language and a set of guidelines supported by a tool to guide them in specifying system requirements. Abstract : A framework, CSRMF, for requirements specification in collaborative environments is introduced. An improved language, CSRML v2, specifies requirements of collaboration and awareness. CSRMF is put in practice by modelling the requirements of a collaborative computer game.